1999
DOI: 10.1093/bja/82.6.881
|View full text |Cite
|
Sign up to set email alerts
|

Combined epidural-spinal opioid-free anaesthesia and analgesia for hysterectomy

Abstract: Postoperative nausea and vomiting (PONV) are major problems after gynaecological surgery. We studied 40 patients undergoing total abdominal hysterectomy, allocated randomly to receive opioid-free epidural-spinal anaesthesia or general anaesthesia with continuous epidural bupivacaine 15 mg h-1 or continuous bupivacaine 10 mg h-1 with epidural morphine 0.2 mg h-1, respectively, for postoperative analgesia. Nausea, vomiting, pain and bowel function were scored on 4-point scales for 3 days. Patients undergoing gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0
2

Year Published

1999
1999
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 19 publications
2
20
0
2
Order By: Relevance
“…25,26 One can note that the incidence of PONV following SAB in our study is higher in both the intervention and control groups than that in the reported literature. 8,13,16 We attribute this to the major gynaecological surgery and female sex that we chose in our study as both are considered as significant risk factors for PONV in themselves. 3,4 Presence of significant proportion of high risk patients (i.e.…”
Section: -11mentioning
confidence: 99%
“…25,26 One can note that the incidence of PONV following SAB in our study is higher in both the intervention and control groups than that in the reported literature. 8,13,16 We attribute this to the major gynaecological surgery and female sex that we chose in our study as both are considered as significant risk factors for PONV in themselves. 3,4 Presence of significant proportion of high risk patients (i.e.…”
Section: -11mentioning
confidence: 99%
“…Compared with general anesthesia with an opioid-based analgesic technique, spinal anesthesia reduces PONV only if no or low-dose (60 mg) intrathecal morphine is used. 33,119 Most studies using epidural analgesia for major gynecologic surgery combine this technique with general anesthesia, and this might not reduce PONV. Callesen and colleagues 119 compared PONV rates between an opioid-free combined spinalepidural (CSE) technique (local anesthetic alone) and a general anesthetic group with epidural analgesia (local anesthetic and opioid) in patients undergoing hysterectomy.…”
Section: Strategies To Reduce the Baseline Risk Of Postoperative Nausmentioning
confidence: 99%
“…До недавнего времени многие исследователи склоня лись к мнению о том, что регионарные методы обезболивания наиболее безопасны с точки зрения риска развития ПОТР [44]. Основой для этого послужила возможность при исполь зовании регионарной анестезии существенно снизить потреб ность в опиоидных анальгетиках, являющихся ведущим анес тезиологическим фактором риска ПОТР [45].…”
Section: современное состояние проблемы профилактики потрunclassified
“…Основой для этого послужила возможность при исполь зовании регионарной анестезии существенно снизить потреб ность в опиоидных анальгетиках, являющихся ведущим анес тезиологическим фактором риска ПОТР [45]. Кроме того, уменьшение дозы опиоидов и симпатическая блокада позволя ют оказывать стимулирующее влияние на моторику ЖКТ, что также благотворно сказывается на снижении ПОТР [44]. Од нако, при всех положительных аспектах, на фоне нейроакси альной блокады нередко имеют место относительная гипово лемия и гипотензия, которые часто нуждаются в коррекции вазопрессорами.…”
Section: современное состояние проблемы профилактики потрunclassified